Tracheal Transection—A Novel Airway Management - Fleißner, Felix; Timm, Max Eike; Lang, Carl Philipp; Lenarz, Thomas; Kühn, Christian; Jaeger, Daniel Benjamin (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background Traumatic injury of the trachea is rare, especially complete transection. Its operative revision requires an interdisciplinary approach.Case Description We hereby present a rare case of complete transection of the trachea by accident. To stabilize the patient and to allow for safe surgery, veno-venous extracorporeal support was initiated via the subclavian artery and the femoral vein. The patient was subsequently operated, and the trachea re-anastomosed with favorable outcome.Conclusion This rare case of an accidental transection of the trachea shows the importance of a good emergency rescue chain and the ability to facilitate interdisciplinary approaches in tertiary hospitals.
Keywords: airway; extracorporeal life support; trachea; emergency room